Improving Indonesian Digital History Usage of Junior High School Students with Audiovisual Media - Amir Syarifuddin; Reka Seprina (Indonesian Journal of Multidisciplinary Science, 2021)
Listening, as one form of language skills, is an early and basic skills of language learning processes of humans. Listening skills made ??the news because this type of research is somewhat less skill to get attention. The main problem in this research is how to improve the ability to hear the Indonesian news in audio-visual media (TV) at the Junior High School seventh grade students Adhyaksa 1 Jambi. The aim is to determine the ability of Indonesian-language news on student following the student's behavior changes, after the use of audio visual media with Samba method, giving tasks, and methods of discussion. Listening to the news consists of extensive listening that is more free, and intensive in nature and need more targeted surveillance. This research into classroom action research (CAR), the sample in this study were the students who take as many as 10 people from 30 students. Technique of data collecting is done through tests and non-test (interview, oservasi and documentation). Furthermore, the data were analyzed with quantitative and qualitative approaches.